The role of cargo transshipment in the relationship between routing and added value - Dias, Edilson Ramos; Moori, Roberto Giro; Morais, Roberto Ramos de; Vitorino Filho, Valdir Antonio (Revista de Administração da UFSM, 2020)
The aim of this article was to verify the impact of cargo transshipment on the relationship between routing and value addition of companies specialized in the road transport of long steels for civil construction. Cargo transshipment is a process of loading and unloading, fractional of products, that consumes time, causes disruption to the industrial activities, commercial and mainly, generates costs inadequately. Considering this context, a research of an exploratory nature of the quantitative type was carried out, in which a sample of 74 transport companies, linked to the steel and independent mills, were used. The collected data, treated by modeling in structural equations using the Partial Least Squares – Path Modeling (PLS-PM), revealed that the transshipment, partially, mediates the relationship between routing and value addition. From this result, it was evidenced that transport managers still need to evolve in the processes of cargo transshipments, through managerial training and elaboration of solutions, involving loading and unloading of products, which are vital for the addition of logistic value to the construction industry.